Perancangan Layout Kerja Menggunakan Analisis Studi Gerak untuk Meningkatkan Efisisensi Waktu Siklus - Muhammad Choiru Zulfa; Dwi Retna Sulistyawati (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Finishing workstations have two activities: cleaning and painting. Irregular work layouts cause time wasted just to move the product to be worked on. In addition, there is no permanent work layout arrangement or placement of work objects so that every day there is a change in work layout makes workers have to make adjustments again, so this will waste time and will reduce the productive time of each worker at the painting work station. The purpose of this study is to design an improvement layout that can be used for cleaning and painting work using the motion study method. The results of the motion study analysis obtained a repair work layout combining two cleaning and painting jobs into one repair layout with the placement of workpieces and work equipment according to the needs of the right and left hands, so that the resulting work movement is more effective and increases cycle time efficiency.